2014
DOI: 10.1122/1.4893586
|View full text |Cite
|
Sign up to set email alerts
|

Magnetorheological effect in the magnetic field oriented along the vorticity

Abstract: International audienceIn this work, we have studied the magnetorheological (MR) fluid rheology in the magnetic field parallel to the fluid vorticity. Experimentally, the MR fluid flow was realized in the Couette coaxial cylinder geometry with the magnetic field parallel to the symmetry axis. The rheological measurements were compared to those obtained in the cone-plate geometry with the magnetic field perpendicular to the lower rheometer plate. Experiments revealed a quasi-Bingham behavior in both geometries w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…As a result, the improvement of the MR effect in bi-component suspensions is more noticeable for cylindrical Couette geometry, in agreement with experiments. 4) and ( 8)) are calculated as a function of the magnetic field H using finite element simulations [18,29] The simulation results for f m and χ a , have been fitted by the following expressions, valid in the range of the magnetic field intensities, 0 30 H ≤ ≤ kA/m: ( )…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the improvement of the MR effect in bi-component suspensions is more noticeable for cylindrical Couette geometry, in agreement with experiments. 4) and ( 8)) are calculated as a function of the magnetic field H using finite element simulations [18,29] The simulation results for f m and χ a , have been fitted by the following expressions, valid in the range of the magnetic field intensities, 0 30 H ≤ ≤ kA/m: ( )…”
Section: Discussionmentioning
confidence: 99%
“…In addition to it, magnetic interactions between aggregates may induce stochastic fluctuations of their orientation and result in a supplementary contribution to the yield stress, coming from stochastic interaction torques. These fluctuations may be regarded as an effective rotary diffusion process, which is likely responsible for the unexpectedly high yield stress when the magnetic field is parallel to either the suspension velocity or the vorticity [19,29].…”
Section: A Qualitative Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…133,134 In this particular geometry, the formation of Taylor vortex flows was reported by Güth and Maas. 134 Furthermore, the magnetorheological behavior of MRFs when the field is oriented in the vorticity direction was investigated by Kuzhir et al 135 They reported an unexpected high MR response that was explained by stochastic fluctuations of positions and orientations of the particle aggregates. The fluctuations were modeled as a rotary diffusion process with a diffusion constant proportional to the mean square interaction torque.…”
Section: Review Soft Mattermentioning
confidence: 99%